1998
DOI: 10.1007/bf03173104
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ and fathers’ well-being, parenting styles, and their children’s cognitive and behavioural strategies at primary school

Abstract: Kaisa Aunola University ojHelsinki, FinlandOne-hundred and five 6-to 7-year-old children were given a test meas uring their helpl essness, fa ilure expec tatio ns, task-irrelevant beha viour, lack of p ersist ence and search fo r social suppo rt in a classroom setting in order to examine the impact ofpar ental well-being a nd parentin g styles on the childre n's cog nitive and behavioural strategies at school. Both par ents were also asked to fill in scales measuring their depression, parenting stress and pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…Specifically, it has been demonstrated that parenting efficacy is negatively related to coercive parenting and positively related to parental responsiveness, involvement, and monitoring (e.g., Bondy and Mash 1999;Gondoli and Silverberg 1997;Shumow and Lomax 2002). Similarly, a positive association between parenting stress and authoritarian or harsh parenting has been found (e.g., Deater-Deckard and Scarr 1996;Emery and Tuer 1993); parenting stress also has been shown to be associated with less maternal responsiveness and affection, as well as less parental supervision (Onatsu-Arvilommi et al 1998;Ritchie and Holden 1998).…”
Section: Depression Parenting-specific Factors and Parenting Behaviormentioning
confidence: 88%
See 1 more Smart Citation
“…Specifically, it has been demonstrated that parenting efficacy is negatively related to coercive parenting and positively related to parental responsiveness, involvement, and monitoring (e.g., Bondy and Mash 1999;Gondoli and Silverberg 1997;Shumow and Lomax 2002). Similarly, a positive association between parenting stress and authoritarian or harsh parenting has been found (e.g., Deater-Deckard and Scarr 1996;Emery and Tuer 1993); parenting stress also has been shown to be associated with less maternal responsiveness and affection, as well as less parental supervision (Onatsu-Arvilommi et al 1998;Ritchie and Holden 1998).…”
Section: Depression Parenting-specific Factors and Parenting Behaviormentioning
confidence: 88%
“…Current findings provide initial evidence that maternal parenting stress, as well as locus of control mediate this association when examining lax parenting. Parenting stress as a mediator is not surprising given that previous research has found a positive association between maternal depression and negative perceptions of parenting (for a review, see Downey and Coyne 1990), as well as a positive association between parenting stress and lax parenting (e.g., less responsiveness and supervision; Onatsu-Arvilommi et al 1998;Ritchie and Holden 1998). Maternal locus of control as a mediator of the maternal depressive symptomatology-lax parenting association is interesting.…”
Section: Maternal Depressive Symptomatology and Lax Parentingmentioning
confidence: 91%
“…For example, parents' general beliefs and related child-rearing practices may provide a basis for their children's own selfperceptions (Frome & Eccles, 1998;Parsons et a1., 1982;Stevenson & Newman, 1986) and, consequently, their task-focused or task-avoidant behavior, which is then reflected in their mathematical performance. Another possibility is that parents' general beliefs about their children's academic competendes are assodated with authoritative parenting styles (Murphey, 1992), the effective scaffolding (Pratt, Green, MacVicar, & Bountrogianni, 1992), and rational guidance (Maccoby & Martin, 1983), which have been shown to motivate children's active problem solving attempts and task-focused behavior (Ginsburg & Bronstein, 1993;Onatsu-Arvilommi, Nurmi, & Aunola, 1998), and high subsequent performance.…”
Section: Discussionmentioning
confidence: 99%
“…], the NEPSY, the Boston Naming Test). Many of the measures had been translated earlier, and Finnish reliability and validity data were available from earlier research projects (e.g., the Parenting related stress; the Beck Depression Inventory; the Child Rearing Practices Report; see OnatsuArvilommi, Nurmi, & Aunola, 1998). Some of the measures were translated into Finnish during the longitudinal follow-up and local norms were then collected in conjunction with the research process (e.g., the MacArthur Communicative Development Inventory).…”
Section: Methodsmentioning
confidence: 99%